Análise do ambiente e modelagem da favorabilidade de ocorrência de Faveiro-de-Wilson (Dimorphandra wilsonii rizzini) na região da Bacia do Córrego Marinheiro em Minas Gerais - Max Paulo Rocha Pereira (2018)
Biodiversity is a consequence of a set of evolutionary forces that act by modifying characteristics across thousands of years, besides the interactions occurring withins pecies and between them and their respective environments. The extinction of forest tree species directly threatens the maintenance of its biodiversity. This phenomenon is becoming notorious in debates about environmental changes, especially when the threaten is mainly caused by anthropic action and its consequences. Therefore, studies to characterize threatened species’ environmentare offundamental importance for species maintenance, provision of data to support restoration actions or even the establishment of new communities. The Faveiro-de-wilson (DimorphandrawilsoniiRizzini) is a Brazilianforest treespecies that belongs to the Fabaceae family and it is part of the list of critically endangered forest tree species of Brazil. This species is part of the original flora of two Brazilian biomes: Atlantic Forest and Cerrado (Brazilian Savannah) and it has specimens cataloged in the regions of Rio das Velhas, Paraopeba and Rio Pará in Minas Gerais. The present study aims to: (1) characterize theenvironment with cataloged specimens of Faveiro-de-wilson in the region of the CórregoMarinheiro’s basin(SeteLagoas – Minas Gerais, Brazil);(2) identify a pattern with favorable elements for the basin’sregion, (3) identify locations where it is possible to find samples of this tree, as well as indicate favorable locations to plant new individuals. Two campaigns were carriedout to collect soil and characterize the area. Data analyses revealed that the occurrenceof the Faveiro-de-wilson in the region of the CórregoMarinheiro basin is mainlyassociated with the rugged hill landscape, with the soil classes “Latossolo Vermelho eutrófico” (LVe), “Latossolo Vermelho Amarelo” (LVA) and “CabissoloHaplico” (CX), with low nutrientand high clay content. The model showed that the region presenting elements more favorable to the development of Faveiro-de-wilson was found at thesouth of the basin. The area presents an extensive region of medium to highfavorability indicating the basin as a priorityregion for recovery projects or even for thedevelopment of new communities of D. wilsonii.